Arterial anastomotic pseudoaneurysms in renal transplants: Case series and a scoping review - Ajay Kumar Dabas, DNB; Vishal Singh, DNB; Brijesh Biswas, DNB; Manvendu Jha, DNB; Amit Agrawal, DNB; Amit Shah, DNB; Puneet Aggarwal, DNB; Aditya Gupta, MCh; Ajay Kumar Sharma, MS, FRCS (JVS-Vascular Insights)
Objective: Anastomotic pseudoaneurysms (APs) in renal transplants are rare. Definite guidelines for its management are lacking. A case series and a technique of in-vivo cooling are presented, and the literature is reviewed to help making informed decisions. Methods: This is a retrospective analysis of all the patients who developed APs following renal transplants done between 2013 and 2023. PubMed and Scopus were searched for key words: pseudoaneurysm, aneurysm, arteritis, rupture, renal-transplant, allograft, kidney, mycotic, and fungal/infective. APs or bleeding from transplanted renal artery or anastomosis were included. APs secondary to transplanted renal artery stenosis, intervention, adjacent organ infection, pregnancy, intrarenal pseudoaneurysms, multiorgan transplants, unknown donor status and non-functional grafts were excluded. Results: Eight patients developed APs out of 714 transplants. The technique of in vivo cooling helped save one allograft. Six allografts were explanted. One patient died suddenly at home. After literature search, 199 cases were analyzed. One hundred sixty-four presented within 90 days of transplant (group A), 21 between 91 and 365 days (group B), and 14 after 365 days (group C). APs was evident in 111, and 88 presented with bleeding/hemorrhagic shock, including three deaths. Infective etiology was confirmed by histopathology or culture in 156 cases; Candida, Aspergillus, and Pseudomonas were the most common microbes. However, only 101 had clinical sepsis. Fifty-one had symptoms due to compression of adjacent artery/vein/nerve. Fifty-nine allografts (group A, 38; group B, 9; group C, 12) were saved out of 82 attempted. Nephrectomy with/without arterial reconstruction was done in 115, with recurrence in 26. There were 26 deaths, and all were in group A. Conclusions: APs in renal transplants though rare, result in high mortality and graft loss. Most occur within a year of transplant. Despite infective etiology, features of sepsis can be absent. Recurrence is high following salvage attempt or nephrectomy.